PENGARUH PEMBERIAN TEPUNG LIMBAH IKAN LAYANG (Decapterus macrosoma) DALAM RANSUM TERHADAP PERTUMBUHAN AYAM BROILER (Gallus domesticus L.var.Cobb) - Purwati, Sri; Khoirunnisa, Afifah; Kurniawati, Zenia Lutfi; Pribadi, Teguh (BIOEDUKASI (Jurnal Pendidikan Biologi), 2024)
The current problem for farmers is the gap between chicken feed consumption and broiler chicken meat weight due to inadequate feed quality. To increase meat production, additional nutrients are needed in broiler chicken feed. This research aims to determine the effect of adding flying fish waste meal to the ration on the growth of broiler chickens. This research is an experimental study consisting of four treatments, P0 (control), P1 (5%), P2 (10%), and P3 (15%), with each treatment six times common. The weight gain of broiler chickens increased every week on days 21, 28, 35, and 42. The research results obtained showed that waste fly fish meals can be used as additional feed for broiler chickens. Waste fly fish meal can be used as additional feed for broiler chickens because waste fly fish meal affects the growth of broiler chickens, especially the weight gain of broiler chickens. The provision of flying fish waste meal in the ration in the P3 treatment, namely 15%, shows that there is a real influence on the good growth of broiler chickens so that breeders can use flying fish waste meal as additional feed for broiler chickens.